Food-borne outbreak investigation - Varela Martínez C. (Food safety challenges for mediterranean products, 2015)
The aim of food-borne outbreaks investigation is the identification of the causative agent, the implicated food and the contributory factors that led to the food-borne outbreak, in order to control them and prevent the occurrence of similar outbreaks. There are several steps in the investigation of food-borne outbreaks: outbreak detection, defining and finding cases, generating hypotheses, testing the hypotheses and finding the source, and controlling the outbreak. Different steps can happen at the same time. Pathogens typing information added to the epidemiological data are of great value in the investigation of food-borne outbreaks. At European level, the European Centre for Diseases Prevention and Control (ECDC) is supporting molecular typing initiatives. Web based tools together with social networks can facilitate the investigation of food-borne outbreaks. Investigation of food-borne outbreaks varies among the European Union Member States. Almost half of the food-borne outbreaks reported in Spain are supported by microbiological or epidemiological evidence. In order to improve control and prevention of food-borne outbreaks it would be essential to have more outbreaks supported with strong epidemiological and/or microbiological evidence.
Workshop Food Safety Challenges for Mediterranean Products, 2014/06/10-11, Zaragoza (Spain)